Peran kepala puskesmas SKM dan non SKM dalam meningkatkan kemampuan manajerial puskesmas di kabupaten Oku Timur - Aulawi Aulawi; Riris Andono Ahmad; Mubasysyir Hasanbasri (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Role of the head of public health centers from public health graduates and others on improving managerial skills in East OkuPurposeThis study aimed to understand how public health and non-public health backgrounds affect management skill of primary health care heads, based on ten managerial roles. MethodsThis study was a descriptive study with case-series method, using qualitative methods supported by quantitative data. Eight people were recruited as respondents. They consisted of 4 people that were primary healthcare heads with public health background and 4 people that were primary healthcare heads with non-public health background. Respondents were recruited by purposive sampling. Data collection was performed using in-depth interviews and questionnaire. ResultsPrimary healthcare head with public health background owned more work experience than those with non-public health background. Period of employment in primary health care had an influence on managerial capabilities. There were no significant differences of period of employment in primary health care head positions among the longest with the least to the managerial capabilities. Primary health care heads who had been trained with PIM IV training and other structural positions were known to have better management capabilities, especially compared to the leadership role of those who had not been trained.ConclusionThere was no significant difference in managerial capacity between primary health care heads with public health and those with non-public health background.